1996
DOI: 10.1007/bf02249367
|View full text |Cite
|
Sign up to set email alerts
|

Consumers as community support providers: Issues created by role innovation

Abstract: Using data from a CSP-funded research demonstration project designed to expand vocational services offered by case management teams serving people with serious mental illness, this paper examines the issues created by employing consumers as peer support specialists for the project. Roles and benefits of these positions are analyzed. Challenges experienced by specialists created by serving peers, the structure of the position, the mental health system and the community, and personal issues are analyzed using da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 10 publications
4
90
0
1
Order By: Relevance
“…Benefits such as 'life beyond diagnosis' and a sense of meaning and reciprocity echo those found where people with dementia take part in self-help networks (Clare et al, 2008, Keyes et al, 2014 In terms of challenges, the difficulty of working with clients as colleagues, and the lack of clear PSW roles, is also similar to mental health (Repper and Carter 2011). However, while mental health PSWs tend to report feeling overwhelmed (Mowbray et al, 1996), PSWs with dementia reported the opposite, wanting more opportunities. Also, uniquely to this setting, Note * 'Emergent theme' refers to a theme from the thematic analysis; ** 'Ranked theme refers to theme ranked within the nominal groups process; § 'ranking' refers to ranking of theme within the nominal group in terms of numbers endorsing it (high ranking means more people endorsed it) '-' indicates where no ranked themes representing that particular emergent theme were generated in that group.…”
Section: Discussionmentioning
confidence: 88%
“…Benefits such as 'life beyond diagnosis' and a sense of meaning and reciprocity echo those found where people with dementia take part in self-help networks (Clare et al, 2008, Keyes et al, 2014 In terms of challenges, the difficulty of working with clients as colleagues, and the lack of clear PSW roles, is also similar to mental health (Repper and Carter 2011). However, while mental health PSWs tend to report feeling overwhelmed (Mowbray et al, 1996), PSWs with dementia reported the opposite, wanting more opportunities. Also, uniquely to this setting, Note * 'Emergent theme' refers to a theme from the thematic analysis; ** 'Ranked theme refers to theme ranked within the nominal groups process; § 'ranking' refers to ranking of theme within the nominal group in terms of numbers endorsing it (high ranking means more people endorsed it) '-' indicates where no ranked themes representing that particular emergent theme were generated in that group.…”
Section: Discussionmentioning
confidence: 88%
“…Liaison with entities involved in these activities should be established to enable this process. Intensive community based peer mentoring/sponsorship programs, consumer managed peer support networks and drop-in centers are examples of these services (Carling, 1995;Chinman, Weingarten, Stayner, & Davidson, 2001;Cheung & Sun, 2001;Fisher, 1994a;Kurtz, 1990;Mowbray et al, 1996;Rootes & Aanes, 1992). Access Facilitating Processes.…”
Section: Supportsmentioning
confidence: 98%
“…They can increase patient access to needed services by assisting patients to navigate through fragmented service systems and performing, often more than other staff, support activities such as transportation, childcare, and life-skills development. 43 In addition, CPs can help move services toward a recovery orientation in several ways. 27,44 They often serve as an unofficial liaison to the non<consumer staff, interpreting, and in some cases mediating, between staff and patient.…”
Section: Cps and System Factorsmentioning
confidence: 99%